New Challenging Scenarios in Transcatheter Aortic Valve Implantation: Valve-in-valve, Bicuspid and Native Aortic Regurgitation - Sandra Santos-Martínez; Ignacio J Amat-Santos (European Cardiology Review)
Transcatheter aortic valve implantation (TAVI) is the most frequently performed structural technique in the field of interventional cardiology. Initially, this procedure was only used in patients with severe symptomatic aortic stenosis and prohibitive risk. Now, barely one decade after its introduction, TAVI indications extend to low- and intermediate-risk patients. Despite these advances, several challenging scenarios are still on the periphery of the evidence base for TAVI. These include valve-in-valve procedures, lower-risk patients with bicuspid aortic valve and the treatment of pure aortic regurgitation. Whereas the valve-in-valve indication has expanded rapidly, evidence for the use of TAVI compared with conventional surgery for bicuspid aortic valve is limited, including the best choice of device should TAVI be used. Evidence for TAVI in pure aortic regurgitation is still anecdotal because of suboptimal outcomes. Operators worldwide have described variations in the TAVI procedural technique to achieve commissural alignment and to minimise the rate of pacemaker use through cusp overlap implantation. In light of the potential clinical benefits, this may also be an area of further development. This review aims to discuss the current evidence available supporting the use of TAVI for these new indications.